2013
DOI: 10.1177/001440291307900201
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practices and Implementation Science in Special Education

Abstract: Establishing a process for identifying evidence-based practices (EBPs) in special education has been a significant advance for the field because it has the potential for generating more effective educational programs and producing more positive outcomes for students with disabilities. However, the potential benefit of EBPs is bounded by the quality, reach, and maintenance of implementation. The cross-disciplinary field of implementation science has great relevance for translating the promise of EBPs into posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
356
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(372 citation statements)
references
References 31 publications
6
356
0
10
Order By: Relevance
“…This research highlights the challenges when translating evidence-based approaches to practice, whereby rigid fidelity to the intended program implementation can result in a lack of adherence, yet incomplete implementation may not yield the benefits that have been demonstrated in studies (Cook & Odom, 2013). It is important to acknowledge that the feasibility of implementing evidence-based approaches is moderated by factors such as classroom context and characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…This research highlights the challenges when translating evidence-based approaches to practice, whereby rigid fidelity to the intended program implementation can result in a lack of adherence, yet incomplete implementation may not yield the benefits that have been demonstrated in studies (Cook & Odom, 2013). It is important to acknowledge that the feasibility of implementing evidence-based approaches is moderated by factors such as classroom context and characteristics.…”
Section: Discussionmentioning
confidence: 95%
“…But how do we get from conducting carefully designed studies, writing, and reading research papers to making a difference to children's lives? The research-practice gap and how to bridge it is a significant concern for professions, no less within the educational field (e.g., Cook & Odom, 2013;Nuthall, 2004). This gap refers to the challenge of translating new research findings into cutting-edge practices that school psychologists and teachers can use in the classroom (e.g., De Corte, 2000;Slavin, 2002).…”
Section: Lisa Marks Woolfsonmentioning
confidence: 99%
“…It is reported that today many children with multiple disabilities are accepted by large masses, regardless of the degree and complexity of their inadequacy, to take advantage of the best possible training interventions (Cook & Odom, 2013;Foreman, Arthur-Kelly, Bennett, Neilands, & Colyvas, 2014). In the case of multiple disabilities of blind autistic children the same researchers stated that the aims involved in educational interventions were significantly different from those of typical-progressing children.…”
Section: Visual Impairment and Autism Spectrum Disordermentioning
confidence: 99%